A left lung abscess with a displaced subsegmental bronchus and anomalous pulmonary artery and vein: a case report - Ohtaka, Kazuto (Surg Case Rep, 2019)
BACKGROUND: Since a displaced bronchus related to the left upper lobe is an uncommon anatomical anomaly, it has a risk of being accidentally resected during left upper lobe resection unless they are identified preoperatively. A case of video-assisted thoracic surgery (VATS) segmentectomy that was safely performed under preoperative identification of a displaced subsegmental bronchus and anomalous pulmonary vessels is presented. CASE PRESENTATION: A 48-year-old woman visited our hospital because of an abnormal shadow on a radiograph on a health check. The chest computed tomography (CT) showed a multicystic mass with a diameter of 35 mm on dorsal interlobar parenchyma between the S(1+2) and S(6) segments in the left lung. The three-dimensional (3D) CT with multiplanar reconstruction showed that B(1+2)b+c passed to the dorsal side of the left main pulmonary artery (PA), which was considered a displaced bronchus. The branch of A(6) arose from the left main PA at the level of the branches of A(3) and A(1+2), more proximal than the normal anatomy, and passed to the dorsal side of a displaced B(1+2)b+c. The branch of V(1+2) passed between B(6) and the bronchus to the basal segment and joined V(6) at the dorsal side of the pulmonary hilum. Intraoperative findings of the anatomy of the bronchi and pulmonary vessels were exactly the same as the preoperative 3D CT findings, so segmentectomy of S(1+2)b+c and S(6) by VATS was performed safely. Then there were accessory fissures between S(1+2) and S(3) and between S(6) and the basal segment. The pathological diagnosis was a left lung abscess. CONCLUSIONS: A preoperative 3D CT may be helpful for identifying anatomical anomalies. An anatomical anomaly should be suspected if accessory fissure is found during surgery.